The missionary role of mainstream Christianity: Towards a narrative paradigm for social integration of minorities in pluralistic post-apartheid South Africa - Klaasen, John (HTS teologiese studies, 2015)
This article attempts to add to the existing approaches of practical theology and specifically to the missionary approaches of mainline churches towards immigrants. This is an attempt to enhance the mission amongst immigrants by critically engaging with the two approaches, namely: mainstream and margins and pillarization. Notwithstanding the important contributions that these two approaches make to tolerance, integration and cohesion of differences I seek to point out some serious limitations of the two approaches. These limitations include social coercion, co-option, relativism and loss of identity. Considering these limitations a third approach, the narrative approach, takes serious community, tradition and symbol for more effective mission amongst immigrants by mainline churches. Social cohesion, a more realistic reality and integrated communities are some of the consequences of this approach when doing missionary activities amongst immigrants.